2022
DOI: 10.1111/ene.15222
|View full text |Cite
|
Sign up to set email alerts
|

Motor and respiratory decline in patients with late onset Pompe disease after cessation of enzyme replacement therapy during COVID‐19 pandemic

Abstract: Background and purpose: Data on interruption of enzyme replacement therapy (ERT) are scarce in late onset Pompe disease. Due to the COVID-19 crisis, eight neuromuscular reference centers in France were obligated to stop the treatment for 31 patients. Methods:We collected the motor and respiratory data from our French registry, before COVID-19 and at treatment restart.Results: In 2.2 months (mean), patients showed a significant deterioration of 37 m (mean) in the 6-min walk test and a loss of 210 ml (mean) of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In our study population, a cessation of ERT due to the pandemic was more common in patients residing in France. This corresponds with the uncertainty of ERT treatment during the pandemic already having been described in a French population [ 34 ]. This study concluded that interruption of ERT, even as short as a few months (mean 2.2 months), worsens a patient’s motor and respiratory function.…”
Section: Discussionmentioning
confidence: 65%
“…In our study population, a cessation of ERT due to the pandemic was more common in patients residing in France. This corresponds with the uncertainty of ERT treatment during the pandemic already having been described in a French population [ 34 ]. This study concluded that interruption of ERT, even as short as a few months (mean 2.2 months), worsens a patient’s motor and respiratory function.…”
Section: Discussionmentioning
confidence: 65%
“…11 They also confirmed that the 6MWT was more sensitive than ActivLim ("Activity Limitations"). 17,18 The MFM scale has proved useful and is widely used to assess muscle function. It can be used to evaluate disease severity, regardless of disease stage, including, in particular, the D1 dimension, which evaluates standing activities and transfers, the score for which is well correlated with 6MWT and MMT results.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating Pompe disease showed similar results, the interruption of therapy due to the pandemic worsened patients’ motor and respiratory function [ 3 ].…”
Section: Introductionmentioning
confidence: 88%